Responsible innovation in health and health system sustainability: Insights from health innovators’ views and practices - Lehoux, Pascale; Silva, Hudson P; Rocha de Oliveira, Robson; Sabio, Renata P; Malas, Kathy (Health Services Management Research, 2021)
Although healthcare managers make increasingly difficult decisions about health innovations, the way they may interact with innovators to foster health system sustainability remains underexplored. Drawing on the Responsible Innovation in Health (RIH) framework, this paper analyses interviews ( n=37) with Canadian and Brazilian innovators to identify: how they operationalize inclusive design processes; what influences the responsiveness of their innovation to system-level challenges; and how they consider the level and intensity of care required by their innovation. Our qualitative findings indicate that innovators seek to: 1) engage stakeholders at an early ideation stage through context-specific methods combining both formal and informal strategies; 2) address specific system-level benefits but often struggle with the positioning of their solution within the health system; and 3) mitigate staff shortages in specialized care, increase general practitioners’ capacity or patients and informal caregivers’ autonomy. These findings provide empirical insights on how healthcare managers can promote and organize collaborative processes that harness innovation towards more sustainable health systems. By adopting a RIH-oriented managerial role, they can set in place more inclusive design processes, articulate key system-level challenges, and help innovators adjust the level and intensity of care required by their innovation.
Keywords: Libre accès; Publication UdeM

Cadre de référence en transfert de connaissances pour leurs utilisations judicieuses et le soutien à l’innovation - Marie-France, Lafond (2015)
Dans le but d’atteindre une des orientations stratégiques de l’établissement « d’être un établissement de première ligne à vocation universitaire, chef de file en matière de développement et de soutien aux pratiques de qualité et aux pratiques novatrices » 1 , l’établissement s’est doté d’une politique institutionnelle de la recherche, de l’évaluation et du transfert de connaissances 2pour assurer la réalisation d’activités de développement et d’utilisation des connaissances de haut niveau (recherche, évaluation et transfert de connaissances) et ainsi, contribuer à l’amélioration continue de la qualité des soins et des services et à l’innovation en première ligne. Le transfert de connaissances constitue une dimension importante de la mission universitaire de l’établissement. Le CSSS de la Vieille-Capitale a fait du transfert de connaissances un domaine d’expertise à investir. Ce volet de la mission universitaire est en développement au Québec. Afin de poursuivre le développement des connaissances dans ce domaine, l’équipe responsable du transfert s’est étroitement associée aux chercheurs et aux partenaires de l’axe transversal sur le transfert de connaissances au sein du centre de recherche sur les soins et les services de première ligne de l’Université Laval (CERSSPL-UL) ainsi qu’à d’autres chercheurs reconnus dans le domaine au Québec. Les activités de transfert de connaissances sont conçues et structurées de façon à assurer un arrimage étroit entre les milieux de pratique et de gestion de l’établissement et l’équipe de recherche et sa programmation, et ce, en cohérence avec les orientations stratégiques de l’établissement. Le transfert de connaissances concerne un ensemble d’acteurs impliqués dans le développement et l’utilisation des meilleures connaissances pour qu’elles soient mises au service de la population et procurent les retombées attendues au plan de l’amélioration continue de la qualité et de l’innovation. Les chercheurs, le personnel, les gestionnaires, les médecins, les sages-femmes, les stagiaires, les usagers et leurs proches, les bénévoles, les partenaires détiennent des savoirs riches et diversifiés qui font quotidiennement l’objet de transfert de connaissances.
Keywords: Co-production; Innovation; Libre accès; Partenariat; Politiques publiques; Québec; Santé

Espaces et lieux d’humanisation : quel statut accorder aux productions techno-scientifiques? - Pelchat, Yolande (Anthropologie et Sociétés, 2003)
La multiplication des innovations techno-scientifiques marque de façon toute particulière le monde contemporain. Quel statut doit-on leur accorder? L’espace actuel de la réflexion critique ne les rend-il pas d’emblée suspectes, sujettes à condamnation, coupables d’une perte de lien social et d’humanité? Axées sur l’efficacité, porteuses d’uniformisation et de contraintes à l’expression du subjectif, ces innovations ne sont-elles pas, par nature, déshumanisantes? Dans cet article, l’auteure tente d’ouvrir d’autres espaces de réflexion pour penser les techno-sciences et la façon dont elles interviennent dans le débat sur la déshumanisation et la réhumanisation. Tirant profit d’une recherche à travers laquelle elle a suivi le travail d’invention d’une nouvelle méthode contraceptive, l’auteure fait valoir la portée, mais aussi les difficultés, d’une démarche qui met en doute les frontières apparemment hermétiques et infranchissables entre ce qui relève du monde des choses et ce qui relève de l’humain.
Publisher: Département d'anthropologie de l'Université Laval
Keywords: Biotechnologie; Libre accès; Santé; Techno-sciences; technosciences

Comment collaborer avec les municipalités ? Un guide pratique pour les acteurs de la santé publique - Morestin, Florence; publique, Un guide pratique pour les acteurs de la santé; Centre de collaboration nationale sur les politiques publiques et la santé (CCNPPS - Centre de collaboration nationale sur les politiques publiques et la santé, 2020)
Au-delà des municipalités, le guide pourrait être utile pour inspirer l’approche de partenaire, tout particulièrement dans le secteur public.
Keywords: Libre accès; Municipalités; Partenariat; Québec; Santé publique

Approcher les municipalités pour partager des connaissances : les conseils de fonctionnaires municipaux aux acteurs de la santé publique - Morestin, Florence (CCNPPS - Centre de collaboration nationale sur les politiques publiques et la santé, 2019)
En effectuant une revue de littérature sur les différents types de conseillers des décideurs politiques (incluant les fonctionnaires), leur rapport aux connaissances scientifiques et leur rôle dans l’élaboration des politiques publiques (Morestin, 2017), nous n’avons trouvé aucune étude portant sur les fonctionnaires municipaux au Canada. Nous avons donc réalisé des entrevues avec des fonctionnaires de quelques municipalités canadiennes. Dans ce document, nous présentons leur point de vue en réponse à des questions que peuvent se poser les acteurs de la santé publique : - Si je souhaite partager des connaissances avec une municipalité, qui approcher? - Que fait déjà la municipalité dans mon domaine de travail? - Comment établir le premier contact? - Quels types de connaissances les fonctionnaires municipaux jugent-ils utiles? - Comment entretenir de bonnes interactions? - Quel échéancier prévoir? - Officialiser une collaboration avec une municipalité : pourquoi, et sous quelle forme?
ISBN : 978-2-550-83744-2
Keywords: Libre accès; Municipalités; Politiques publiques; Québec; Santé publique

Assessing and promoting partnership between patients and health-care professionals: Co-construction of the CADICEE tool for patients and their relatives - Pomey, Marie-Pascale; Clavel, Nathalie; Normandin, Louise; Grande, Claudio Del; Ghadiri, Djahanchah Philip; Fernandez-McAuley, Isabel; Boivin, Antoine; Flora, Luigi; Janvier, Annie; Karazivan, Philippe; Pelletier, Jean-François; Fernandez, Nicolas; et al. (Health Expectations, 2021)
Context Partnership between patients and health-care professionals (HCPs) is a concept that needs a valid, practical measure to facilitate its use by patients and HCPs. Objective To co-construct a tool for measuring the degree of partnership between patients and HCPs. Design The CADICEE tool was developed in four steps: (1) generate key dimensions of patient partnership in clinical care; (2) co-construct the tool; (3) assess face and content validity from patients’ and HCPs’ viewpoints; and (4) assess the usability of the tool and explore its measurement performance. Results The CADICEE tool comprises 24 items under 7 dimensions: 1) relationship of Confidence or trust between the patient and the HCPs; 2) patient Autonomy; 3) patient participation in Decisions related to care; 4) shared Information on patient health status or care; 5) patient personal Context; 6) Empathy; and 7) recognition of Expertise. Assessment of the tool's usability and measurement performance showed, in a convenience sample of 246 patients and relatives, high face validity, acceptability and relevance for both patients and HCPs, as well as good construct validity. Conclusions The CADICEE tool is developed in co-construction with patients to evaluate the degree of partnership in care desired by patients in their relationship with HCPs. The tool can be used in various clinical contexts and in different health-care settings. Patient or Public Contribution Patients were involved in determining the importance of constructing this questionnaire. They co-constructed it, pre-tested it and were part of the entire questionnaire development process. Three patients participated in the writing of the article.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/hex.13253
Keywords: Co-création; Libre accès; Partenariat; Partenariat avec le patient; Publication UdeM

Documentary research on social innovation in health in Latin America. - Castro-Arroyave, D. M.; Duque-Paz, L. F. (Infectious Diseases of Poverty, 2020)
Background: Identifying social innovation in health initiatives, promoting quality of life through them, and transforming current health conditions demand the knowledge, comprehension and appropriation of the theoretical and methodological developments of this concept. Academic developments in social innovation have mainly occurred in and been documented for English-speaking countries, although...
Publisher: BioMed Central Ltd
Keywords: Amérique latine; Innovation sociale; Libre accès; Santé

Social Innovation For Health Research: Development of the SIFHR Checklist - Kpokiri, Eneyi E.; Chen, Elizabeth; Li, Jingjing; Payne, Sarah; Shrestha, Priyanka; Afsana, Kaosar; Amazigo, Uche; Awor, Phyllis; de Lavison, Jean-Francois; Khan, Saqif; Mier-Alpaño, Jana; Ong, Alberto; et al. (PLOS Medicine, 2021)
Background Social innovations in health are inclusive solutions to address the healthcare delivery gap that meet the needs of end users through a multi-stakeholder, community-engaged process. While social innovations for health have shown promise in closing the healthcare delivery gap, more research is needed to evaluate, scale up, and sustain social innovation. Research checklists can standardize and improve reporting of research findings, promote transparency, and increase replicability of study results and findings. Methods and findings The research checklist was developed through a 3-step community-engaged process, including a global open call for ideas, a scoping review, and a 3-round modified Delphi process. The call for entries solicited checklists and related items and was open between November 27, 2019 and February 1, 2020. In addition to the open call submissions and scoping review findings, a 17-item Social Innovation For Health Research (SIFHR) Checklist was developed based on the Template for Intervention Description and Replication (TIDieR) Checklist. The checklist was then refined during 3 rounds of Delphi surveys conducted between May and June 2020. The resulting checklist will facilitate more complete and transparent reporting, increase end-user engagement, and help assess social innovation projects. A limitation of the open call was requiring internet access, which likely discouraged participation of some subgroups. Conclusions The SIFHR Checklist will strengthen the reporting of social innovation for health research studies. More research is needed on social innovation for health.
Table 2 - intéressante à l’étape d’organiser son projet
Keywords: Innovation inclusive; Innovation sociale; Libre accès; Santé